Shipping in changing climates. (January 2017) - Larkin, Alice; Smith, Tristan; Wrobel, Paul
Abstract: The shipping industry faces an uncertain future, as the climate change challenges faced by all sectors become increasingly urgent and apparent. If a quantitative interpretation of the goals laid out in the Paris Agreement is applied, shipping, along with all sectors combusting fossil fuel, faces substantial challenges in order to successfully decarbonise over the coming decades. Targeted at addressing gaps in knowledge and understanding across technical, operational and demand-side changes, this collection of articles presents some of the latest analysis to consider the opportunities available, and barriers to be overcome, to enable shipping's low carbon transition and the sustainability of global trade.